(untitled) (Economics and region, 2022)
The article examines trends in the consumption of all types of meat, as well as poultry meat in particular. It was found that the development of the poultry industry over the past ten years has led to the strengthening of the positions of the regional markets of poultry products, the increase in the volume of poultry production, and the strengthening of export positions. The dynamics of the supply of poultry meat increased rapidly in the period from 2010, when the volume of production amounted to 631.2 thousand tons, and comparing it with 2021, it is more than half – 1373.5 thousand tons, respectively. The positive dynamics of changes in the diet of the population both in Ukraine as a whole and in individual regions were revealed. At the same time, the growth of poultry meat consumption in such regions as the Western and Southern regions is twice as high as the growth of meat consumption by all types, and in such regions as the Eastern, Central and Northern regions, despite lower growth rates compared to the Western and Southern regions, the growth rate of poultry meat consumption exceeds 3-4 times. It was determined that even such positive dynamics do not ensure the compliance of meat consumption indicators with the minimum approved national standards. It was found that neither the reduction of the population in the regions from 2 to 4.5%, nor the significant increase in the average price of chicken meat (from 81% to 92%) did not affect the rate of growth of market capacity. The rise in poultry meat prices has caused a continuous increase in production costs for many items. Therefore, the main reason for such a rapid increase in the market capacity of poultry products remains that the index of price growth for other types of meat and food products significantly exceeds the level of price growth for poultry meat. The gradual increase in the cost of poultry products is caused by the constant increase in prices for direct material costs, services of third-party organizations, prices for fuel and lubricants, an increase in grain prices, an increase in the exchange rate of foreign currency, an increase in the price of imported veterinary drugs, wear and tear of the material and technical base and an increase in depreciation , which, in turn, entails an increase in consumer prices for the corresponding products.